Smartphone-assisted guided self-help cognitive behavioral therapy for young people with distressing voices (SmartVoices): study protocol for a randomized controlled trial - Cavelti, Marialuisa; Kaeser, Janko M.; Lerch, Stefan; Bauer, Stephanie; Moessner, Markus; Berger, Thomas; Hayward, Mark D.; Kaess, Michael (Trials, 2022)
The long-standing view that auditory verbal hallucinations (AVH) or hearing voices is a sign of schizophrenia has been challenged by research demonstrating that they lie on a continuum ranging from normal to pathological experience related to distress and need for care. Hearing voices is more prevalent in adolescence than in later life, and hearing voices during adolescence indicates a risk for severe psychopathology, functional impairments, and suicide later in life. While there is increasing evidence for the efficacy of cognitive behavioral therapy for voices (CBTv) in adults with schizophrenia, research on psychological treatments for youth with distressing voices has been scarce. The aim of the current study is to examine the efficacy of CBTv, delivered using smartphone-based Ecological Momentary Assessment Intervention (EMI) in a transdiagnostic sample of youth.
Gesehen am 18.01.2023